Chest X-Ray Photo and Pathogenic Bacteria Distribution in Pneumonia Patients: A Literature Review - Monica Cherlady Anastasia; Ade Dharmawan (Green Publisher Indonesia, 2024)
Pneumonia is an acute infectious or inflammatory disease affecting the lung parenchyma that can be caused by microorganisms such as bacteria, viruses, and fungi. This study aims to determine the image of thorax photos and the distribution of pathogenic bacteria in pneumonia patients, as well as to see the image of thorax photos in certain pathogens. The method in this study was to search for articles through Google Scholar and Pubmed. The results showed that the distribution of pathogenic bacteria in pneumonia cases varied, but the most common bacteria causing pneumonia were Streptococcus pneumoniae, Klebsiella pneumoniae, and Mycoplasma pneumonia. The thorax photographs were also quite diverse, and the most common results were consolidation, infiltrates, and pleural effusion. In patients with pneumonia caused by Mycoplasma pneumoniae, the most common thorax images are lobar pneumonia or lobar consolidation.